The Role of Grandmothers in Child-Raising in the Era of Urbanization: Transformation of Traditional Family Values in Medan City - Topan Bilardo; Haslinda Haslinda (Yayasan Zia Salsabila, 2026)
Urbanization in Medan, a metropolitan city, has brought significant changes to family structure and function, particularly in childcare practices. The increasing involvement of grandmothers as primary caregivers represents a family adaptation to economic pressures and the limited time of working parents (Central Bureau of Statistics, 2023; UN-Habitat, 2020). This study aims to analyze the transformation of grandmothers' roles in childcare and their implications for changes in traditional family values. The study used a qualitative approach using literature review methods. The results indicate that grandmothers have shifted from symbolic figures to strategic actors in childcare, as well as agents of cultural value transmission (Chen et al., 2011; Bengtson, 2001). Furthermore, intergenerational value negotiations have resulted in hybrid forms of family values.